2008
DOI: 10.1155/2008/754951
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Active Vibration Control in Truss Structures Considering Uncertainties in System Parameters

Abstract: This paper deals with the study of algorithms for robust active vibration control in flexible structures considering uncertainties in system parameters. It became an area of enormous interest, mainly due to the countless demands of optimal performance in mechanical systems as aircraft, aerospace, and automotive structures. An important and difficult problem for designing active vibration control is to get a representative dynamic model. Generally, this model can be obtained using finite element method (FEM) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…In this robust controller design, the modelling uncertainty is included to prevent undesirable behaviours of the controller due to the modelling errors. Spillover is a problem when the controller excites the unmodelled modes [21,22]. The mathematical model of the smart beam constructed in section 3.1 for the first three out-ofplane bending modes of the smart beam is chosen as the nominal plant for the controller design.…”
Section: Robust Controller Design For Piezoelectric Sensor/actuator Pairmentioning
confidence: 99%
“…In this robust controller design, the modelling uncertainty is included to prevent undesirable behaviours of the controller due to the modelling errors. Spillover is a problem when the controller excites the unmodelled modes [21,22]. The mathematical model of the smart beam constructed in section 3.1 for the first three out-ofplane bending modes of the smart beam is chosen as the nominal plant for the controller design.…”
Section: Robust Controller Design For Piezoelectric Sensor/actuator Pairmentioning
confidence: 99%
“…There are various control algorithms enabling the control of the smart trusses presented in the scientific articles. The results of the laboratory research of LQR control of the smart truss are shown in [3]. The truss was 0,03 [m] high and 0,06 [m] wide.…”
Section: Introductionmentioning
confidence: 99%